Diseño de un sistema de video vigilancia y seguridad para el sistema integrado de transporte urbano de la ciudad de Loja (SITU). - Veintimilla Ocampo, Paula Juliana (2016)
This project in order to get an academic title plan a solution to the Integrated Urban Transport System of Loja city by a Video Surveillance System and Security System Design for bus stations to achieve a systematic and organized development of this project, it has been structured in different sections. In the first part all the information will be presented it will explain how the urban transport system will work and how many bus stations there will be, and it also explains the bus routes. There is a brief exposure of video surveillance system by IP cameras, it shows the main types of cameras, video compressions standards and adequate places to storage them. This design lets to apply the latest technology of a network system using optical fiber, in addition to the standardized passive access networks and specific recommendations related to the GPON system. In the third section the analysis and design of video surveillance system is done, this is considered on the basis of the inspection carried out at each station and sub - station in the city of Loja, after an analysis of the best manufacturers of devices IP technology, select the one that best fits our design, this parameter and technical specifications of the selected device bandwidth and storage capacity is calculated. Therefore, the security system is designed selecting an alarm panel which will be used in every bus station and this system will monitor and get the expected security; as well as people are inside or when ones are closed to control and prevent damages. Finally the conclusion and the most important recommendations are exposed, as a result of this research.